2021
DOI: 10.1111/acel.13510
|View full text |Cite
|
Sign up to set email alerts
|

Dietary citrate supplementation enhances longevity, metabolic health, and memory performance through promoting ketogenesis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…However, after QWJR intervention, citric acid decreased and cis-aconitic acid increased, returning to normal. Citric acid is not only the primary source of adenosine triphosphate (ATP) but also an inflammatory signal whose accumulation may help generate pro-inflammatory mediators, such as NO and reactive oxygen species (ROS) ( Infantino et al, 2014 ; Fan et al, 2021 ). In viral pneumonia, the TCA cycle in M1-type macrophages is blocked, leading to citric acid accumulation and succinate.…”
Section: Discussionmentioning
confidence: 99%
“…However, after QWJR intervention, citric acid decreased and cis-aconitic acid increased, returning to normal. Citric acid is not only the primary source of adenosine triphosphate (ATP) but also an inflammatory signal whose accumulation may help generate pro-inflammatory mediators, such as NO and reactive oxygen species (ROS) ( Infantino et al, 2014 ; Fan et al, 2021 ). In viral pneumonia, the TCA cycle in M1-type macrophages is blocked, leading to citric acid accumulation and succinate.…”
Section: Discussionmentioning
confidence: 99%
“…Other nutrient sensors, such as AMP-activated protein kinase (AMPK) and sirtuin signaling, tend to be deregulated with aging. AMPK, a key regulator of cellular energy, is activated in C. elegans during nutrient-deprivationor low-energetic conditions and extends the lifespan [ 26 , 27 ], Drosophila [ 28 ] and mammals [ 29 ] by inhibiting TORC1 activity, activating autophagy, and improving cellular stress resistance. Sirtuins, a class of histone deacetylases involved in lifespan regulation, protect against the aging process by enhancing cellular stress resistance [ 30 ].…”
Section: Deregulated Nutrient Sensingmentioning
confidence: 99%
“…However, the long-term effects of exogenous citrate administration on overall health has not been well explored. In a recent study, we demonstrated that dietary citrate supplementation was associated with lifespan extension, decreased hemolymph glucose and triglyceride, and reduced ATP/ADP ratio in fruit flies fed on a relatively highcalorie diet [1]. Furthermore, we found that AMPactivated protein kinase (AMPK) was activated and target of rapamycin (TOR) signaling was suppressed in these flies.…”
mentioning
confidence: 93%